Aspergirls : empowering females with Asperger Syndrome - Simone, Rudy (Jessica Kingsley Publishers, 2010)
Girls with Asperger's Syndrome are less frequently diagnosed than boys, and even once symptoms have been recognised, help is often not readily available. The image of coping well presented by AS females of any age can often mask difficulties, deficits, challenges, and loneliness. This is a must-have handbook written by an Aspergirl for Aspergirls, young and old. Rudy Simone guides you through every aspect of both personal and professional life, from early recollections of blame, guilt, and savant skills, to friendships, romance and marriage. Employment, career, rituals and routines are also covered, along with depression, meltdowns and being misunderstood. Including the reflections of over thirty-five women diagnosed as on the spectrum, as well as some partners and parents, Rudy identifies recurring struggles and areas where Aspergirls need validation, information and advice. As they recount their stories, anecdotes, and wisdom, she highlights how differences between males and females on the spectrum are mostly a matter of perception, rejecting negative views of Aspergirls and empowering them to lead happy and fulfilled lives. This book will be essential reading for females of any age diagnosed with AS, and those who think they might be on the spectrum. It will also be of interest to partners and loved ones of Aspergirls, and anybody interested either professionally or academically in Asperger's Syndrome. -- Publisher description